AKUNTABILITAS ADOL-ATUKU, SANDA (GADAI) DAN AHUTANGAPIHUTANG DALAM KITAB KUTARA MANAWA DHARMASASTRA PADA MASA KEEMASAN MAJAPAHIT - Fakhruddin Asy’ari ; Prof. Eko Ganis Sukoharsono, SE., M.Com(Hons)., Ph.D,Yeney Widya Prihatiningtias, SE., MSA., DBA, Ak., CA (Thesis Akuntansi FEB - UB, 2018)
This study aims to understand accountability regulated in the book of Kutara Manawa Dharmasastra, particularly regarding Adol-Atuku (sales and purchase), Sanda (collateral loan), and Ahutang-Apihutang (debts), during the golden age of Majapahit Empire. The objects of this ethnoarchaeological study are the National Museum of Indonesia, the Archeological Heritage Center of Trowulan, the Majapahit Museum, the MpuTantular Museum, and related libraries. The data of this study was collected through documentation and interviews with two informants